Solve: (10^4 × 0.1^-3 × 10^-8) ÷ 1000 Using Scientific Notation

Question

Solve the following problem:

1040.131081000=? \frac{10^4\cdot0.1^{-3}\cdot10^{-8}}{1000}=\text{?}

Video Solution

Solution Steps

00:00 Simplify the following problem
00:06 Convert the decimal to a fraction
00:10 Break down 1000 to 10 to the power of 3
00:13 In order to eliminate the negative exponents
00:16 Flip the numerator and the denominator and the exponent will become positive
00:19 We'll apply this formula to our exercise
00:35 Reduce wherever possible
00:42 When multiplying powers with equal bases
00:46 The power of the result equals the sum of the powers
00:49 We'll apply this formula to our exercise and proceed to add up the powers
00:55 This is the same formula as the first one but with 1 in the denominator
01:01 This is the solution

Step-by-Step Solution

Begin by writing the problem and converting the decimal fraction in the problem to a simple fraction:

1040.131081000=104(110)31081000=? \frac{10^4\cdot0.1^{-3}\cdot10^{-8}}{1000}=\frac{10^4\cdot(\frac{1}{10})^{-3}\cdot10^{-8}}{1000}=\text{?}

Next

a. We'll use the law of exponents for negative exponents:

an=1an a^{-n}=\frac{1}{a^n}

b. Note that the number 1000 is a power of the number 10:

1000=103 1000=10^3

Apply the law of exponents from 'a' and the information from 'b' to the problem:

104(110)31081000=104(101)3108103 \frac{10^4\cdot(\frac{1}{10})^{-3}\cdot10^{-8}}{1000}=\frac{10^4\cdot(10^{-1})^{-3}\cdot10^{-8}}{10^3}

We applied the law of exponents from 'a' to the term inside the parentheses of the middle term in the fraction's numerator. We applied the information from 'b' to the fraction's denominator,

Next, let's recall the law of exponents for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

And we'll apply this law to the same term we dealt with until now in the expression that we obtained in the last step:

104(101)3108103=10410(1)(3)108103=104103108103 \frac{10^4\cdot(10^{-1})^{-3}\cdot10^{-8}}{10^3}=\frac{10^4\cdot10^{(-1)\cdot(-3)}\cdot10^{-8}}{10^3}=\frac{10^4\cdot10^3\cdot10^{-8}}{10^3}

We applied the above law of exponents to the middle term in the numerator carefully, since the term in parentheses has a negative exponent. Hence we used parentheses and then proceeded to simplify the resulting expression,

Note that we can reduce the middle term in the fraction's numerator with the fraction's denominator. This is possible due to the fact that a multiplication operation exists between all terms in the fraction's numerator. Let's proceed to reduce:

104103108103=104108 \frac{10^4\cdot10^3\cdot10^{-8}}{10^3}=10^4\cdot10^{-8}

Let's summarize the various steps to our solution so far:

104(110)31081000=104(101)3108103=104103108103=104108 \frac{10^4\cdot(\frac{1}{10})^{-3}\cdot10^{-8}}{1000}=\frac{10^4\cdot(10^{-1})^{-3}\cdot10^{-8}}{10^3} = \frac{10^4\cdot10^3\cdot10^{-8}}{10^3} = 10^4\cdot10^{-8}

Remember the law of exponents for multiplication of terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n}

Let's apply this law to the expression that we obtained in the last step:

104108=104+(8)1048=104 10^4\cdot10^{-8}=10^{4+(-8)}10^{4-8}=10^{-4}

Now let's once again apply the law of exponents for negative exponents mentioned in 'a' above:

104=1104=110000=0.0001 10^{-4}=\frac{1}{10^4}=\frac{1}{10000}=0.0001

When in the third step we calculated the numerical result of raising 10 to the power of 4 in the fraction's denominator. In the next step we converted the simple fraction to a decimal fraction,

Let's summarize the various steps of our solution so far:

104(110)31081000=104103108103=104=0.0001 \frac{10^4\cdot(\frac{1}{10})^{-3}\cdot10^{-8}}{1000} = \frac{10^4\cdot10^3\cdot10^{-8}}{10^3} = 10^{-4} =0.0001

Therefore the correct answer is answer a.

Answer

0.0001 0.0001